ANALISIS PERILAKU KONSUMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN KOPI di KOPI VOKASI - Doni Sahat Tua Manalu; Andya Nabila Arawinda; Assaidah Nurul; Fitriyani Fitriyani; Khairunnisa Salsabilla; Muhammad Shafwa; Nengri Nengri (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Indonesia occupies the third position as the largest coffee producing country after Brazil and Vietnam. This happens because coffee consumption continues to increase every year, which indicates a change in the lifestyle of Indonesian people. This research aims to analyze the attributes that influence coffee purchasing decisions at Kopi Vocational, analyze consumer attitudes towards purchasing coffee at Kopi Vocational, and analyze the performance of Kopi Vocational in fulfilling the attributes that are important to consumers. Data was obtained from 100 respondents using a purposive sampling method (currently purchasing or having consumed). Data analysis uses descriptive methods, attitude scales, the Fishbein method, and IPA method. The results of the research data show that the majority of respondents are women aged between 18-28 years who work as students with an average income of <Rp. 1,000,000.00. The consumer interest and trust index obtained is in a positive classification with a score of 94.99. The attributes of trust in Vocational Coffee that need to be improved are the facilities and the attributes of trust that must be maintained are taste, price, service, and packaging materials.